1997
DOI: 10.1523/jneurosci.17-10-03455.1997
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate, But Not Dopamine, Stimulates Stress-Activated Protein Kinase and AP-1-Mediated Transcription in Striatal Neurons

Abstract: Drugs that stimulate dopamine and glutamate receptors have been shown to induce the expression of AP-1 proteins (such as c-Fos and c-Jun) in the striatum and to induce binding of these proteins to AP-1 sites on DNA, leading to the hypothesis that AP-1-mediated transcription contributes to the long-term effects of these drugs. To examine this hypothesis, we compared the regulation of AP-1-mediated transcription to the inductions of AP-1-binding activity and genes encoding AP-1 proteins in primary cultures of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
88
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(97 citation statements)
references
References 84 publications
9
88
0
Order By: Relevance
“…In contrast, dopamine (1-100 M) did not induce any significant increase in the luciferase activity (Fig. 9A), a similar result to that observed previously (Schwarzschild et al, 1997). Thus, activation of group I mGluRs can trigger AP-1-mediated transcription in living striatal cells.…”
Section: Dhpg Induces Ap-1-mediated Transcription Via the Jnk Pathwaysupporting
confidence: 89%
See 2 more Smart Citations
“…In contrast, dopamine (1-100 M) did not induce any significant increase in the luciferase activity (Fig. 9A), a similar result to that observed previously (Schwarzschild et al, 1997). Thus, activation of group I mGluRs can trigger AP-1-mediated transcription in living striatal cells.…”
Section: Dhpg Induces Ap-1-mediated Transcription Via the Jnk Pathwaysupporting
confidence: 89%
“…Phospho-c-Jun is a principal dimer in assembling an active transcription factor, AP-1, in striatal neurons in response to glutamate stimulation (Schwarzschild et al, 1997). Given an increased expression of phospho-c-Jun proteins after DHPG stimulation, AP-1 activity could be elevated (see below) to upregulate the AP-1-mediated transcription.…”
Section: Transactivation Of Egf Receptors Is Required For Mglur5-medimentioning
confidence: 99%
See 1 more Smart Citation
“…Excitatory neurotransmission through NMDA receptors usually increases intracellular Ca 2ϩ levels. It has been shown that glutamate-induced Ca 2ϩ influx into neurons activates both ERK (Fiore et al 1993b;Kurino et al 1995;Vanhoutte et al 1999;Schwarzschild et al 1999) and JNK/SAPK (Schwarzschild et al 1997) signaling pathways. In contrast, extracellular Ca 2ϩ was not required for the NMDA-receptor-mediated activation of SAPK in cultured striatal neurons (Schwarzschild et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, the inhibition of ERK1/2 activation has been shown to protect a mouse neuronal cell line and rat primary cortical neurons form oxidative stress-induced neurotoxicity [1] demonstrating a possible involvement in cell death. The JNK signaling cascade has been reported to be activated by a wide range of different oxidants/reductants including hydrogen peroxide [135,218], lipid peroxidation products [6,191], different types of radiation [63], modulators of intracellular glutathione status [145], peroxynitrite [71], glutamate [180], dithiothreitol, and nitric oxide [152]. Although the links between redox status and MAPK signaling have been known for some time, data demonstrating the molecular basis of such links and identifying the sensors in this redox response are few.…”
Section: Mapk Signaling Under Oxidative Stressmentioning
confidence: 99%